Analysis of mathematical inductive reasoning ability reviewed from student learning styles in mathematics learning - Rahayu Tirta Kusumah; Aan Subhan Pamungkas; Jaenudin Jaenudin (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to describe students' mathematical inductive reasoning ability viewed from visual, auditorial, and kinesthetic learning styles in the Sequence and Series material. The type of research used is descriptive research with a qualitative approach. The instruments of this study were mathematical inductive reasoning ability tests, learning style questionnaires, and interview guidelines. The subjects of this study were six students of Class XI MIPA-2 SMA Negeri 1 Kota Serang that representing each learning style. The results showed that 1) students with a visual learning style were able to do transductive reasoning, analogies, used relationship patterns to analyze situations, compiled conjectures and could estimate answers, and they were able to explain patterns; 2) students with auditorial learning styles were able to do transductive reasoning, analogies, used relationship patterns to analyze situations, compiled conjectures and could estimate answers; 3) students with a kinesthetic learning style were able to do transductive reasoning, analogies, could use relationship patterns to analyze situations and compiled conjectures, and they were able to make generalizations.